Badan Pertanahan Nasional sebagai Mediator dalam Penyelesaian Sengketa Tanah Pasca Permen ATR/BPN RI No. 21 Tahun 2020 - Muhammad Khaikal Fajri; Erlina Erlina (Lembaga Yasin AlSys, 2026)
Although land disputes in Indonesia have been widely studied, discussions that specifically examine structural conflicts of interest in the dual role of the National Land Agency (BPN) as both certificate issuer and mediator remain limited. This study aims to analyze the authority and position of BPN as a mediator over its own legal products and to examine the legal certainty and executorial force of mediation outcomes based on Regulation of the Minister of ATR/BPN Number 21 of 2020. This study used a normative legal research method with statutory, conceptual, and analytical approaches. The legal materials used included primary legal materials in the form of laws and regulations and court decisions at four judicial levels, secondary legal materials in the form of legal doctrines and previous studies, and tertiary legal materials as supporting sources. Data were collected through library research and analyzed using normative juridical analysis techniques. The results showed that BPN’s mediation authority is facilitative-administrative in nature and contains three forms of structural conflict of interest, namely reputational, informational, and judicial conflicts, which are inherently contrary to the principle of nemo iudex in causa sua. In addition, the Deed of Settlement resulting from BPN mediation has the status only of a private deed without executorial title and has been proven weak at four judicial levels. These findings contribute to the development of administrative law theory and land law, particularly regarding the institutional design of mediation functions and understanding of structural bias in administrative dispute resolution mechanisms. The conclusion of this study affirms the importance of institutional separation of the mediator function and the granting of executorial title through statutory revision. The implications of this study include theoretical contributions to the development of literature on administrative law and land dispute resolution, as well as practical implications for the government and legislative institutions in reforming land mediation regulations to ensure substantive legal certainty and structural impartiality.